Factors Affecting the Adoption of E-Commerce: A Study of the Textile Industry in Wujin, China - Chong, Alain Yee Loong; Ooi, Keng Boon; Tak, Yew King; ShuYang, Zhu (Society for Alliance, Fidelity & Advancement, 2009)
The purpose of this paper is to examine the factors that influence the adoption of e-commerce with emphasis on textile companies in WuJin, China. The factors are organizational readiness, innovation characteristics, government influence and culture. Binary logistic regression was applied to test the research model. The result shows that organizational readiness, innovation characteristics and culture influence the adoption of e-commerce among textile companies in WuJin. As China's culture is different from many western countries, it is found that relationships between organizations, or GuanXi as it is commonly known in China, needs to be established before organizations collaborating with each other are willing to adopt e-commerce. The findings of this study are useful for the Malaysian companies who are interested to adopt e-commerce with their business partners in China.